Por uma geografia do contato interétnico: (re)posicionamento da alteridade indígena na produção da fronteira amazônica - Tatiane de Cássia da Costa Malheiro (Confins)
The indigenous alterity’s place in the production of the Amazonian border is analyzed here from the understanding of a geography of interethnic contact, which involves a symbolic and material repositioning of indigenous peoples; a process historically constructed from distinct meanings, permeated by colonialist relations (internal and external) and founded on violence and expropriation to the indigenous peoples of the region. This relationship is structured on the basis of two distinct and interdependent dimensions, territorial domination and the reproduction of a civilizing project, which, in general, are linked to ways of incorporating the indigenous people into a hegemonic logic and of subordinating their ethnic condition.